Pengaruh Motivasi Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Bagian PPIC Production Planning Inventory Control PT. Ewindo Plant 2 Sumedang - Rahmawati, Rima; Sasangka, Indra; Aghnia, Nadya Larasati (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine Work Motivation, Work Stress, Employee Performance and to determinehow much influence between Work Motivation and Work Stress on Employee Performance at PT.EWINDO Plant 2 Sumedang. This research method used is a quantitative method with the type ofdescriptive verification research with the subject of all employees of PT. EWINDO Plant 2 part of thePPIC Production Planning Inventory Control as many as 37 people to be respondents. From theresults of the study it can be concluded that work motivation simultaneously has a significant positiveeffect on employee performance with the results of the hypothesis test H0 being rejected and Ha beingaccepted. And the results of the research carried out can be seen from the calculation results oftcount> ttable, namely 2.092 > 0.68156. As for work stress simultaneously has a significant negativeeffect on employee performance with the results of the hypothesis test H0 being rejected and Ha beingaccepted. And the results of the research conducted can be seen from the calculation results tcount <ttable, namely -4.216 <0.68156.